Governing Environment Federal Perspective from India and Canada - Sharma, Sanjay (Cambridge Scholars Publishing, 2016)
This book comparatively analyses the federal policies and financing of India and Canada. It examines whether federalism as a system of governance is better suited to deal with environmental questions. It operates from the assumption that federalism can provide an effective solution to the emerging concerns of the environment because it essentially provides a model of disaggregated governance without any extensive and intrusive mark of hierarchy.It presents a uniquely exploration of environmental governance from this hitherto under-researched perspective, and simultaneously, in order to provide a better conceptual understanding, examines the different theories of federalism and modes of distribution of powers, authorities and functions. Given their symmetrical federal experiences, India and Canada naturally qualify as the domain of study, with both being known as twin federal nations. Issues of environment have been factorised and classified according to their critical significance in terms of policy choices. The combinatorial structure has been evaluated in terms of better federal management of environment. In the process, many new dimensions of federalism and environment have emerged, which may contribute to the critical mass of knowledge on the subject.This book makes a departure from the general mono-construction of the environment as a restricted unit of knowledge available only to a specialist. Broadly following an interdisciplinary logic of formation of idea, this study is highly relevant in generating a new perspective on environmental research. It defines environment as a system which requires careful redrafting and reworking of three structures of relationships, namely between man and environment, between resource community and the state, and between inter-governmental contestations